PERCEIVED TRENDS IN RAINFALL VARIABILITY: A STUDY OF CROP FARMERS IN YANDEV DISTRICT, BENUE STATE, NIGERIA - Oga, Grace Eneche; Tarhule, Daniel Aondover; Hemba, Samuel Terlumun; Mustapha, Fatimah Bello (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
Agriculture serves as the cornerstone of both local livelihoods and the national Gross Domestic Product (GDP) across numerous African nations (Mandelsohn et al., 2008). Nigeria, predominantly agrarian, witnesses an engagement of approximately 70% - 80% of its population in subsistence-level agricultural activities (National Report, 2006; Tunde, Usman, and Olaweopo, 2011). Remarkably, the agricultural sector constitutes a significant one-third of the country's GDP (Muhammad-Lawal and Atte, 2006).